Caps for sale : a tale of a peddler, some monkeys, and their monkey business - Slobodkina, Esphyr, 1908- (New York : Harper & Row, 1985)
A band of mischievous monkeys steals every one of a peddler's caps while he takes a nap under a tree.
Wilson's Children
Elem. School Library Collection
School Library Journal
3.1
K-3
Keywords: Hats -- Fiction; Peddlers and peddling -- Fiction; Monkeys -- Fiction; Monkeys -- Fiction